SOCIAL AND CULTURAL FACTORS INFLUENCING HELP-SEEKING BEHAVIOUR OF WOMEN WITH DISABILITIES - Prasita Ayu Widyaningtyas; Rita Damayanti; Roma Yuliana; Putri Rahmadani; Artha Budi Susila Duarsa; Ahmad Fauzi; Gracia Kelengi Sembiring (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Women with disabilities face a substantially higher risk of sexual violence compared to non-disabled women, yet their access to help is frequently hindered by social and cultural barriers that remain underexplored in the Indonesian local context. This study aimed to explore the social and cultural factors influencing help-seeking behavior among women with disabilities who survived sexual violence in Yogyakarta. Methods: A qualitative case study design was used. Two women with physical and sensory disabilities aged 15-49 years under the auspices of Organization X in Yogyakarta served as primary informants, supported by one counselor as key informants. Data were collected through in-depth interviews with source triangulation and analyzed using thematic analysis. Two major themes emerged: social factors (disability stigma, social marginalization, and economic vulnerability) and cultural factors (patriarchal norms, Javanese family honor culture, and victim-blaming attitudes). Social and cultural factors substantially impede help-seeking among women with disabilities who survived sexual violence. Community based, disability and gender sensitive interventions and stronger local protective policies are urgently needed